The Effect of Internal Control System on Financial Accountability of Regional Public Service Agency of Public Health Center (BLUD Puskesmas) During Covid-19 Pandemic - Suwardi; Achmad Choerudin; Widodo Feriyanto (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research aims to study the effect of internal control system (SPI) on Financial Accountability of Regional Public Service Agency of Public Health Center (BLUD Puskesmas). The research took place in Karanganyar Regency of Central Java Province, Indonesia. Data of research was collected from all Public Health Centers (Puskesmas) in Regency during pandemic period. The institutional analysis unit consisted of 21 Puskesmas with 125 respondents. The analysis technique used was a multiple regression. Results: (1) information and communication, and monitoring affect positively the financial accountability, and (2) control environment, risk estimation, and controlling activity do not show significant effectThis research aims to study the effect of internal control system (SPI) on Financial Accountability of Regional Public Service Agency of Public Health Center (BLUD Puskesmas). The research took place in Karanganyar Regency of Central Java Province, Indonesia. Data of research was collected from all Public Health Centers (Puskesmas) in Regency during pandemic period. The institutional analysis unit consisted of 21 Puskesmas with 125 respondents. The analysis technique used was a multiple regression. Results: (1) information and communication, and monitoring affect positively the financial accountability, and (2) control environment, risk estimation, and controlling activity do not show significant effect